Influence of Vestibular Bevel on the Success of Traumatized Teeth Restorations: Single-Blind Randomized Controlled Trial - Preliminary Results with 6-Months Follow-Up - Marcela Baraúna Magno; Lucas Alves Jural; Matheus Melo Pithon; Lucianne Cople Maia (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the influence of cavosurface vestibular bevel (CSVB) application on the clinical success (CS) of class IV restorations of traumatized permanent teeth, the influence of the number of fracture angles and dental trauma recurrence (DTR) on the restorations retention rate (RRR) and incidence of pulp necrosis (PN). Material and Methods: Fifty-seven children and adolescents with enamel and dentin fractures requiring C-IV restorations were randomly allocated in groups with CSVB and without CSVB. The primary outcomes were the CS of restorations, evaluated using modified USPHS criteria, and the incidence of PN after a 6-months follow-up. As secondary outcomes, the influence of the number of fractured angles and the DTR on the RRR and on the incidence of PN were evaluated (p>0.05). Results: Of 57 children and adolescents, 74 teeth were restored, and 71 completed the six-month follow-up analysis. Teeth restored with and without CSVB displayed similar CS as well as the same incidence of PN (p>0.05). The number of fractured angles did not influence the RRR and DTR was not associated with PN (p>0.05). DTR was associated with a lower RRR (p<0.001). Conclusion: Cavosurface vestibular bevel did not influence the clinical success of Class IV restorations or incidence of PN after 6-months follow-up. DTR did not influence the incidence of pulp necrosis, but did negatively influence the restorations retention rate. The number of fracture angles did not influenced in the restorations retention rate.